Burn documentation in emergency department files and its impact on admission or discharge - Ori Berger; Mor Mendelson; Ran Talisman (Elsevier, 2023)
Background: Accurate burn injury documentation is crucial for management. The four crucial elements of burn injury documentation are location, etiology, degree, and total body surface area. In our emergency room (ER), ER physicians primarily provide initial care. We aim to evaluate their assessment of the 4 Crucial Elements and their correlation to in-house care or discharge. Methods: A retrospective ER charts study was conducted using ICD-9 codes for burn injury. Every tenth file was retrieved for detailed review, and burns' characteristics and management were examined. Chi-squared test was used on the data for analysis. Results: We examined 301 patient files. Location was always stated. Only 43% had a complete description. Etiology was missing in 7%, burn degree in 18.5%, and TBSA in 67.5% of files. Patients with full descriptions had a statistically significant higher admission rate than those with partial documentation (P < 0.035), indicating a relationship between full documentation and the need for admission. Conclusions: The study found incomplete documentation of burn injuries by non-burn physicians in the ER, leading to an impact on patient care decisions. There is a need for education and training to improve documentation quality, and the inclusion of burn-care rotations in medical education and residency programs.